Halting the expansion of pasture in the Brazilian Amazon - zu Ermgassen, Erasmus K.H.J.; Adami, Marcos; Chaves, Michel E.D. [UNESP]; Garcia, Andrea; Hodel, Leonie (Elsevier, 2024)
There are growing hopes that improved supply chain traceability can break the link between pasture-based cattle ranching and deforestation in the Amazon. Here, we caution that supply chains are but one part of the puzzle—a combination of policies are needed to end the expansion of pasture.